Natural Product Inhibitors of Ubiquitin Conjugation and Deconjugation - Hess, Wilfried (Studies in Natural Products Chemistry, 2016)
The ubiquitin–proteasome system has been recognized as fundamental toward protein turnover in eukaryotic cells. The system comprises the ubiquitin conjugation machinery consisting of an enzyme cascade of E1, E2, and E3 enzymes, the deubiquitinases (DUBs) and the proteasome, a multisubunit protease complex acting through an N-terminal threonine protease mechanism. A number of natural product inhibitors of the proteasome have been studied in detail and these inhibitors and their derivatives have been highly valuable in developing our understanding of this system. These efforts culminated in the successful development of bortezomib as a pharmacological agent used clinically as a cancer therapeutic in the treatment of multiple myeloma. This review is focused on natural product inhibitors of the enzymes involved in intracellular ubiquitin conjugation (ubiquitin-activating enzyme E1, ubiquitin-conjugating enzyme E2, ubiquitin ligase E3) and ubiquitin deconjugation (DUBs). Members of both of these enzyme systems have been proposed as pharmacological targets for cancer therapy and several other diseases. Furthermore compounds with activities toward enzymes from the analogous ubiquitin-like (Ubl) protein families have been identified for SUMO and NEDD8. To date natural product inhibitors have been described for members of each of these protein families and were isolated from plant, fungal, animal, and microbial sources. Insights into the mechanism of action of natural products and their derivatives will enhance our understanding of this complex system and will improve our ability to rationally design novel inhibitors. The increased availability of assays and research tools for the study of protein ubiquitination, deubiquitination, and Ubl proteins will contribute to the discovery of more potent and selective compounds. We expect that these studies will stimulate development of further potential pharmacological agents in this area.